MANFAAT DAN PENGEMBANGAN TEKNOLOGI UMBI PORANG (AMORPHOPHALLUS MUELLERI BLUME)MELALUI METODE PENGERINGAN: BENEFITS AND TECHNOLOGY DEVELOPMENT OF PORANG BULBS (AMORPHOPHALLUS MUELLERI BLUME) THROUGH DRYING METHOD - Serapin Putri, Putu Ayu Viona (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2022)
Porang tubers are one of the most popular plant cultivations in the international market. The benefits and advantages of pora ng tuber cultivation make porang tubers one of the strengths to be able to reduce imports. The benefits of this cultivation will certainly be felt by farmers. Because of the great benefits felt, it would be very appropriate if porang tubers would be strongly assoc iated with technology, especially in the drying method. This study aims to be able to s how descriptively the method of drying porang tubers from conventional things that still depend on solar heat to technology-based to the creation of a drying machine. The application of technology will certainly facilitate the community in accelerating the production of porang tubers. Optimization to achieve time efficiency is certainly the biggest advantage. Until finally the factors inhibiting production will be minimized. Keywords: Porang tubers, drying machine, solar heat